La recerca sobre el factor edat en llengües estrangeres no és independentista - Naves, Teresa (Caplletra. Revista Internacional de Filologia, 2008)
In order to guarantee better results in the acquisition of foreign languages, there is a generalized trend all over the world which states that the learning of a foreign language should be done as early as possible.This article aims at exploring several questions related to this subject: (1) To discuss the origin of expectations of linguistic policies which imply that “regarding languages, the earlier the better”; (2) the reason for the differences in the results obtained in studies with apprentices in natural contexts and in contexts of foreign language learning; and finally (3) to show the results of the research on the learning of English by Catalan students, in writing in particular, carried out in the Acquisition Research Group of Second Languages(GRAL) at the University of Barcelona.